ATP-citrate lyase inhibitor improves ectopic lipid accumulation in the kidney in a db/db mouse model - Zhan, Zishun; Li, Aimei; Zhang, Wei; Wu, Xueqin; He, Jinrong; Li, Zhi; Li, Yanchun; Sun, Jian; Zhang, Hao (Frontiers in Endocrinology, 2022)
Aim: We evaluated a novel treatment for obesity-related renal injury, ATP-citrate lyase (ACL) inhibitor, to attenuate ectopic lipid accumulation (ELA) in the kidney and the ensuing inflammation. Materials and Methods: ACL inhibitor was administered intragastrically to 12-week-old db/db mice, for 30 days. ELA manifestation was observed by staining kidney sections with oil red O, and the differences in tissue lipid metabolites were assessed by mass spectrometry. The anti-obesity and renoprotection effects of ACL inhibitors were observed by histological examination as well as multiple biochemical assays. Results: Using the AutoDock-Vina application, we determined that among the four known ACL inhibitors (SB-204990, ETC-1002, NDI-091143, and BMS-303141), BMS-303141 had the highest affinity for ACL, and it reduced ACL expression in kidney of db/db mice. We reported that BMS-303141 administration could decrease the levels of serum lipid and renal lipogenic enzymes acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), HMG-CoA reductase (HMGCR), and diminish renal ELA in db/db mice. In addition, we found that as ELA reduced, the renal injury was improved, and the renal inflammation and tubulointerstitial fibrosis were alleviated. Conclusion: ACL inhibitor BMS-303141 is protective against obesity-related renal injury.